The eﬀectiveness of deep dry needling combined with neural mobilisation in patients with sciatic hyperalgesia: a case report - Shanmugam, Sukumar; Kandakurti, Praveen Kumar; Durairaj, Satheeskumar (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. Sciatic hyperalgesia is a rare chronic pain condition caused by sciatic nerve constriction at focal areas extend-ing from the lower back to the foot. The aim of this report was to study the eﬀectiveness of deep dry needling combined with neural mobilisation in patients with sciatic hyperalgesia.Methods. Two middle-aged patients with sciatic hyperalgesia symptoms were assessed and conﬁrmed with intervertebral disc bulge at the lumbar level and tightness of the piriformis and hamstring muscles. Two sessions of deep dry needling and three sessions of sciatic neural mobilisation were employed during the ﬁrst week. Moreover, the patients were instructed to perform home-based neural mobilisation exercises for three consecutive weeks.Results. Signiﬁcant reductions in pain, disability, and fear avoidance behaviour, as well as improvements in movement, were achieved on the eighth day. At one-month follow-up, the patients resumed routine daily activities without pain and movement restriction, which was maintained for six months.Conclusions. These results suggest that deep dry needling combined with neural mobilisation may be an additional therapeutic intervention to relieve the symptoms of sciatic hyperalgesia. However, further clinical trials are necessary to substantiate its eﬀects.
Keywords: sciatica; piriformis syndrome; dry needling; trigger point; neurodynamic